2013
DOI: 10.7203/attic.10.2339
|View full text |Cite
|
Sign up to set email alerts
|

Mejoras cuantitativas y cualitativas de los programas de estancias cortas en el extranjero

Abstract: La participación en estudios a corto plazo en el extranjero se ha incrementado exponencialmente en los Estados Unidos, eclipsando el semestre tradicional o año académico en el extranjero que se programaba en décadas anteriores. Aunque criticado y rechazado por muchos profesores de idiomas y proveedores de estudios en el extranjero, está apareciendo un creciente corpus de investigación en defensa de los programas a corto plazo. El presente estudio de caso examina las ganancias cuantitativas en las orientaciones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Allen and Herron (2003) reported no significant gains in integrative motivation in U.S. undergraduate learners of French after taking part in a short-term program in France. In Ziamandanis (2013), U.S. undergraduates studying Spanish took part in a twoweek program in Costa Rica focusing on the effects of ecotourism. The results of participants' pre-and post-test performance on a test of intercultural development indicated that many of the participants regressed in their attitudes towards cultural difference.…”
Section: Can Short-term Study Abroad Programs Be Effective?mentioning
confidence: 99%
See 1 more Smart Citation
“…Allen and Herron (2003) reported no significant gains in integrative motivation in U.S. undergraduate learners of French after taking part in a short-term program in France. In Ziamandanis (2013), U.S. undergraduates studying Spanish took part in a twoweek program in Costa Rica focusing on the effects of ecotourism. The results of participants' pre-and post-test performance on a test of intercultural development indicated that many of the participants regressed in their attitudes towards cultural difference.…”
Section: Can Short-term Study Abroad Programs Be Effective?mentioning
confidence: 99%
“…As a final note of caution for assessing the program, improvements in intercultural competence and cultural understanding may take months after the program to appear, as in Ziamandanis (2013), where participants initially regressed immediately after the program. This is likely because participants need time to unpack and reflect on their experience abroad.…”
Section: Program Assessmentmentioning
confidence: 99%